Teachers' professional development as a pathway for educational reform in Egypt. Issue 2 (4th March 2017) - El-Bilawi, Nora H.; Nasser, Ilham
Abstract: This study explores teachers' reflections on the professional development (PD) provided by the Egyptian Ministry of Education as part of a national reform plan implemented right before the political changes in Egypt. The study took place in three national language schools and focused on English as Foreign Language teachers' perspectives on the PD and the successes and challenges they faced implementing it. Results highlight teachers' critical reflections on the quality and duration of the PD. Despite the effort, they expressed dissatisfaction with the lack of support and follow up from the administration, in addition to the lack of practical examples that characterized the PD.